Becoming A School Governor and BCS Membership. (13th February 2019) - Hicks, Judith
Abstract: Volunteering as a school governor is challenging but enormously rewarding. As Judith Hicks from the National Governance Association explains, it is a great way to make a difference for young people in your local community.